Morphological revision of the species of Homoeomma Ausserer, 1871 (Araneae: Theraphosidae) from Brazil, Argentina and Uruguay - Galleti-Lima, Arthur; Yamamoto, Flávio U.; Lucas, Sylvia M.; Guadanucci, José Paulo L.; Brescovit, Antonio D. (Zootaxa, 2026)
The Neotropical tarantula genus Homoeomma Ausserer, 1871 is reviewed. After examining type specimens and redescribing several species, H. stradlingi O. Pickard-Cambridge, 1881 and H. strabo (Simon, 1892) are considered junior synonyms of H. familiare Bertkau, 1880; henceforth, the senior synonym of the type species of the genus, and now with a known male representative. H. nigrum is considered nomem dubium. Additionally, Homoeomma hirsutum (Mello-Leitão, 1935) is considered junior synonym of H. montanum (Mello-Leitão, 1923). We also describe the female of H. brasilianum (Chamberlin, 1917). Homoeomma now comprises 12 valid species distributed across Argentina, Brazil, Chile, Colombia, and Uruguay.